Analisis Konten Buku Ajar Bahasa Arab MTs Kelas VII Kurikulum KMA No. 183 2019 - Hasan Syaiful Rizal; Ulfatul Chasanah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
The feasibility of the Arabic textbook is at least assessed from the four aspects imposed by the National Education Standards Agency, namely aspects of language, content, presentation, and graphics. This research examines the content which includes hiwār and qirā'ah aspects in Arabic books published by the Ministry of Religion in 2020 based on the Decree of the Minister of Religion no. 183 2019. The focus of this research is to determine the suitability of the contents of the book with spiritual, social, knowledge and attitude core competencies. This study used a qualitative approach with the type of library research, with primary data in the form of Arabic language textbooks for class VII KMA published in 2020. Data collection techniques were documented, then analyzed using content analysis. The results of this research indicate that there is a match between the contents of the book material and the four core competencies which are the focus of this research.